THE EFFECT OF WORK CONTENT, PRIDE AND GRATITUDE ON JOB SATISFACTION FOR EMPLOYEES OF THE BPJS EMPLOYMENT OFFICE IN ACEH - Puspaliya, Puspaliya; Irmalis, Amsal (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to analyze the effect of work content, honor and gratitude on employee job satisfaction conducted at the BPJS Ketenagakerjaan office in Aceh. In this study, there were 65 samples of the population, namely BPJS Employment employees in Aceh. The data were collected by using an online questionnaire distribution technique and the data analysis in this study was carried out through multiple linear regression analysis. The results of the study show: 1) There is a simultaneous positive and significant effect between work content, pride and gratitude on job satisfaction of the employees of the BPJS Employment Office in Aceh as shown from the F test results of 19.947 and the value of sig. 0.000 . 2) There is a negative and insignificant effect between work content on job satisfaction of BPJS Ketenagakerjaan office employees in Aceh as shown from the t-test results of 1.056 and sig. 0.295. 3) There is a negative and insignificant effect between pride on employee job satisfaction as seen from the results of the t-test of 1.825 and the value of sig. of 0.073. 4) There is a positive and significant effect between gratitude on job satisfaction of BPJS Ketenagakerjaan office employees as shown from the t-test results of 2,356 and sig. 0.022. The results obtained by the regression equation Y = 1.401a + 0.113X1 + 0.284X2 + 0.387X3 + e.